Subsideband Generation Associated with Period-N Pulsations in Tm Soliton Fiber Lasers - Pan Wang; Xiaosheng Xiao; Philippe Grelu; Changxi Yang (IEEE Photonics Journal, 2017)
In mode-locked thulium soliton fiber lasers, we experimentally observe and numerically confirm the formation of numerous dispersive-wave sidebands, following a bifurcation of the pulse dynamics into a stationary short-period pulsation. These resonant sidebands appear in addition to the Gordon-Kelly sidebands that are formed in the stationary mode-locked regime. The origin of these sidebands is discussed, highlighting their complexity that does not comply with a simple modulation instability analysis.